2012
DOI: 10.1016/j.ijscr.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of left paraduodenal hernia in two cases of children

Abstract: Laparoscopic repair of paraduodenal hernia in children and infants is safe and feasible. We recommend the laparoscopic repair as the first surgical option for paraduodenal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…This paper introduces the case of a patient with small bowel obstruction due to left paraduodenal hernia, which was successfully treated by laparoscopic approach and a review of the current scientific literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] concerning the increasingly emerging minimally invasive treatment of this surgical emergency.…”
Section: Introductionmentioning
confidence: 99%
“…This paper introduces the case of a patient with small bowel obstruction due to left paraduodenal hernia, which was successfully treated by laparoscopic approach and a review of the current scientific literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] concerning the increasingly emerging minimally invasive treatment of this surgical emergency.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis is difficult because left paraduodenal hernia is asymptomatic or causes vague symptoms, such as nausea, vomiting, and postprandial pain [ 4 ]. Multi-detector CT is most useful for the diagnosis of the left paraduodenal hernia, and shows clustered dilated small-bowel loops that pass through the dorsal side of the IMV [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery for left paraduodenal hernia should be considered because the lifetime risk of incarceration of left paraduodenal hernia is thought to be up to 50% [ 4 ]. There are two steps in surgical procedures for left paraduodenal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Since Uematsu et al 4 reported the first laparoscopic repair of paraduodenal hernia in 1998, many reports have described laparoscopy as a diagnosis or repair tool for paraduodenal hernia (Table 1). 14,20,[28][29][30][31][32][33][34][35][36][37][38][39][40] Laparoscopic surgery has been implemented in many surgical fields. Several reports have demonstrated feasibility and benefits in terms of cosmetic aspects and reduced pain, rendering SILS an alternative method to conventional and multiport laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the reports that referred to operation operation time ranged from 55 to 180 minutes. 20,34,35,39 In 1 case, paraduodenal hernia recurred 18 months after the operation, and reoperation was required and in another case the inferior mesenteric vein was injured during operation. 20 However, other cases including our case did not result in any complications and the hospital stay was relatively short.…”
Section: Discussionmentioning
confidence: 99%